Pelatihan Pengemasan Produk Wingko Ungu Hasil Produksi Kelompok Usaha Wingko Ungu Desa Banjararum, Kecamatan Kalibawang, Kabupaten Kulon Progo - Herman Legowo; Rizky Wulandari; Dianila Oktyawati (Jurnal Pengabdian dan Pengembangan Masyarakat, 2018)
Banjararum Village is an agropolitan village that has potential in agriculture field such as sweet potato and red dragon fruit. In addition, there are Small Medium Enterprises (SMEs)  as conducted by Kelompok Wanita Tani  Banjararum Village, Kalibawang, Kulonprogo which is producing snack  from agriculture such as wingko purple and red dragon fruit. But they do not have an attractive packaging yet. The purpose of this community service is to provide training and mentoring on wingko products. The method used is the delivery of the concept of an attractive logo and packaging, logo-making training, and packaging training. The result of this activity is the women farmer groups have a knowledge about the logo and packaging are interesting and have an interesting logo and packaging on wingko products. The conclusion of this activity is the implementation of the activity runs smoothly, Kelompok Wanita Tani Banjararum has the knowledge of interesting design and economical.